Optimalisasi Pengelolaan Sampah Berbasis Masyarakat : Implementasi Bank Sampah dan Budidaya Maggot di Dusun Sabatan - Selly Safitri Maharani; Maharani Dara Dinanti; Amelyda Vira Fajarizqy; Susanti Malasari (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
The establishment of a waste bank program in Sabatan Hamlet, Ringinanom Village, Magelang Regency, is one of the solutions to address the increasing household waste problem. This program was carried out through the Community Service Program (KKN) of Tidar University from January to February 2025, with the aim of raising public awareness about the importance of environmentally friendly waste management. This research used a descriptive qualitative method, with data collection techniques including open interviews, field surveys, and focus group discussions (FGD). The program implementation was conducted in four main stages: preparation, socialization, execution, and assistance. During the execution phase, the "UD Sregep" waste bank was successfully established, focusing on the management of paper, plastic bottles, and cans. Additionally, the program successfully integrated inorganic waste management with Black Soldier Fly (BSF) maggot cultivation for organic waste, creating a sustainable waste management system that holds economic value for the community. The program received positive support from various stakeholders, including the community, village government, and other parties, demonstrating its success in improving the welfare of the community through waste utilization.